Flexible planning of assessment, a lever towards assessment for learning? - Yerly, Gonzague; Monney, Nicole (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2022)
The article discusses the contribution of flexible planning of assessment as a lever to support teachers in implementing assessment for learning in the classroom. It proposes a theoretical reflection on the contribution of “flexible” planning, i.e. planning that is thorough and structured (hierarchical) but that also leaves room for adjustments during the interaction (dynamic) and involves the students (interactive). The contribution of the article has been to link the scientific findings on planning the teaching-learning process with those on the assessment of learning. The objectives of this paper are to 1) specify what “flexible” planning of assessment is, 2) to discuss the contributions of such planning in the implementation of assessment for learning in the classroom.